Myocardial iron measurement in thalassemia using cardiac magnetic resonance image processing software - Boonchieng E. (2017)
To assess the iron overload in human tissue especially in the heart of transfusion-dependent thalassemia patients using cardiac magnetic resonance imaging (CMRI) technique has been widely used to evaluate cardiac iron deposition because of its non-invasive procedure. The iron measure from this technique is represent as T2*(T2 Star) value. Cardiac T2*software was developed. The software was measuring T2*value from DICOM image with two algorithm processing components; regions of interest (ROI) identification, and T2*optimization. The software preliminary testing was performed using test cases DICOM image, three times repeating, from both healthy volunteer and thalassemia patient with cardiac iron overload, then compared T2*value with the reference tool (CMRtools with ThalassemiaTools plug-in). Mean T2*value analyzed from healthy volunteer CMRI was 22.36 (±0.94) and 37.10 (±1.62), respectively. While the mean T2*value analyzed from thalassemia patients CMRI was 15.52 (±0.85) and 18.67 (±1.15) in reference software and CMUT2Star software respectively. In conclusion, CMUT2Star produced a higher T2*value than the reference tool. Software has no any errors and no conflict with testing platform. The algorithm in T2*optimization component need to be adjusted in order to produce the accuracy and robust T2*value. ©2012 IEEE.